Pengaruh Penguasaan Mufrodat, Sintaksi Dan Morfologi Dalam Meningkatkan Kemampuan Menerjemah Bahasa Arab-Indonesia Pada Mahasiswa Sastra Arab Universitas Nahdlatul Wathan Mataram - Ahmad Sirojul Hakiki; Budi Ilham; Masdani (An Nazhair: Journal of Arabic Education, 2026)
Arabic - indonesia translation is one of the activities that has its own urgency in indonesia. there are many adherents of Islam in indonesia where the source of the teachings is the al-qur'an and sunnah which use Arabic. this factor makes translation in indonesia very familiar. But so far, translation has a high level of difficulty stemming from various factors such as mufrodat, nahwu, shorf and others. so this study tries to reveal the influence in mastering vocabulary, syntax and morphology in improving the ability to translate Arabic-Indonesian for Arabic literature students at nahdlatul wathan university mataram. The type of this research is causality research with a quantitative approach. This research seeks to reveal the influence exerted by the independent variable on the dependent variable. Then for the location of this research was carried out in Arabic literature, Nahdlatul Wathan University Mataram from August to December. The results are vocabulary, syntax and morphology variables each have a significant effect partially and simultaneously on the variable (Arabic translation ability). statistical results show mastery of vocabulary t count of 2.400> t table 2.064 with a significance value of 0.026 < p-value 0.05. syntax mastery t count of 3.953 > t table value 2.064 with a significance value of 0.001 < p-value 0.05. morphological variables t count of 3.414 > t table 2.064 or a significance value of 0.003 < 0.05. The simultaneous test (F test) shows a significance value of 0.000 < p-value 0.05 or the value of F count 44.746 > F table which is 3.027.